Optimized reactive power support strategy for photovoltaic inverter to intensify the dynamic voltage stability of islanded microgrid. (3rd March 2020) - Afrin, Nadia; Yang, Fuwen; Lu, Junwei
Summary: This study presents an innovative and optimized reactive power support (ORPS) strategy for photovoltaic (PV) inverters to improve the dynamic voltage stability (DVS) of islanded microgrid (MG) with induction motor (IM) load. On the occurrence of the fault, voltage instability (VI) happens due to the low‐inertia IM load and poor ride through capability of PV inverters of MG. Supplement of optimal RPS promptly, without exceeding the rated current value of the inverter, is aimed at the proposed control, to maintain DVS during severe voltage downfall as a result of a fault. Once the profiled voltage value is restored and the necessity of RPS is fulfilled, the PV inverter returns to its prefault power production combination. The detailed model of an inverter‐based islanded MG with IM load is built to examine the DVS, and the theoretical analysis and technical discussion are conducted. A comparison between the conventional and proposed strategies is carried out. From the demonstrated results, employing the proposed ORPS control can provide RPS effectively and helps to improve the DVS. This proposed strategy can also provide an equivalent service as an expensive 610‐kVA dynamic volt‐ampere reactive support device (ie, D‐STATCOM) in the studied MG.